A study of sleep quality and aggression among young adults in Malaysia - Hew, Lai Mun; Wong, Choon Wei (2019)
In Malaysia, there have many young adults’ issues which have related to sleep quality and aggression. Sleep quality can affect the academic performance, individual of psychological and physical health while aggressive behavior was mostly happened in young adults like vandalism. Sleep quality and aggression has proven there have correlated with each other. However, it was not clearly understood there have a correlated with each others. Thus, this study aimed to investigate the sleep quality and aggression among young adults in Malaysia. This is a correlational study that uses a quantitative, cross-sectional research design. A total of three hundred and ninety-two Malaysia young adults were recruited using convenient sampling method. Pittsburgh Sleep Quality Index (PSQI) and Buss-Perry Aggression Questionnaire (BPAQ) were used in this study. Pearson correlation test was used to measure the relationship between both variables which are sleep quality and aggression and the results presented significance. Independent t-test was used to measure between the gender difference and both variables, the results indicated that there was no significant between the male and female in sleep quality but male higher sleep quality than female. Furthermore, another result indicted that there was no significant between the male and female in aggression but male higher aggression level then female. Findings in this study can used as a fundamental of future research. The future study should be focus on different kind of occupation and education background, applying longitudinal design, and stratified random sampling to improve the generalization ability of results.